Arsenic Induced Myocardial Toxicity in Rats: Alleviative Effect of Trichosanthes dioica Fruit. (1st September 2014) - Bhattacharya, Sanjib; Das, Sanjit Kumar; Haldar, Pallab Kanti
ABSTRACT: The present study investigated the alleviative effect of aqueous extract of Trichosanthes dioica fruit (AQTD) against arsenic induced cardiotoxicity in Wistar albino rats. AQTD (50 and 100 mg/kg) was administered orally to rats for 20 consecutive days before oral administration of sodium arsenite (10 mg/kg) for 8 days. Then the body weights, heart weights, hematological profile, serum biochemical profile; myocardial antioxidative parameters viz. lipid peroxidation, reduced and oxidized glutathione, glutathione- S -transferase, glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD), catalase (CAT), and DNA fragmentation were evaluated. Pretreatment with AQTD markedly and significantly normalized body weights, heart weights, hematological profile, serum biochemical profile and significantly modulated all the myocardial antioxidative parameters and reduced DNA fragmentation in arsenic intoxicated rats. Therefore, T. dioica fruit possessed remarkable alleviative effects against arsenic induced myocardial toxicity in Wistar albino rats mediated by amelioration of arsenic induced myocardial oxidative stress by several mechanisms.